Understanding women farmers’ empowerment in climate- stressed smallholder systems: Evidence from a climate-smart cropping system intensification initiative in Indian Sundarbans - Sen, Poulami; Misra, Sanchayeeta; Goswami, Rupal; Sarkar, Sukamal; Ray, Krishnendu; Roy, Kalyan; Mallick, Kousik; Brahmachari, Koushik; Nanda, Manoj K.; Monjardino, Marta; Mainuddin, Mohammed (Ramakrishna Mission Vivekananda Educational and Research Institute, India, 2023)
Climate change poses a profound threat to the wellbeing and sustainability of farming and farm-based livelihoods in fragile socioecological systems. Climatic challenges to farming have often been addressed by diverse forms of sustainable intensification that aim to maximize farm outputs and resource-use efficiency through climate-smart innovations. However, climate change poses specific challenges to women farmers, who play important roles in agri-food systems, often in the absence of their male counterparts who recursively migrate from the climatically challenged regions. In the absence of a gender-sensitive extension and advisory regime, it exacerbates existing gender inequities and limits women farmers’ ability to adjust to changing climatic conditions. Unfortunately, inadequate attention is paid to the gendered outcomes of climate-smart intensifications and cropping-system transformations in smallholder systems. This implies the generation of evidence and insights into the gendered experience and measurements of the program interventions. The current study draws evidence from an international cropping-system-upscaling initiative that engages women farmers from the climatically challenged Sundarbans region in India. To understand the climatesociety-innovation-gender nexus, we measure women farmers’ empowerment and the existing gender gap by employing the comprehensive Women’s Empowerment in Agriculture Index and gender analyses. WEAI evaluates the domains of women farmers’ empowerment and gender analyses help to understand the gender gap in the system. The study outcomes show differential gendered outcomes of the climatesmart interventions and suggest the importance of contextual sociocultural factors shaping the nature and extent of women’s empowerment.